Analisa Ketersediaan Air Dengan menggunakan Gabungan Metode Mock Dan Model Tank Di Kali Samin Kabupaten Karanganyar - Utami, Dessy Dwi; , Gurawan Djati Wibowo, ST., M.Eng; , Ir. Ahmad Karim Fatchan, M.T (2016)
Limitations of the flow data is one of in water management problems that often occured on the water availability analysis. Streams data that exist in Indonesia ranges from 2-4 year, this is caused by several factors, among others hidrometri station damaged by floods, landslides and act of human hands. This is also happensed in the Central Java, that is Samin River. Samin River becomes water source for daily needs, which upstream is located in Karanganyar and downstream is located in Sukoharjo. Based on the analysis of discharge and rainfall data, much of them has been damaged, moreover Samin River has been drought saverel time. The main objective of the research is to analyze the availability of water in a watershed (DAS) using the rain flow model approach combining Mock and Tank Model for establising the rain flow algorithm. One of the model which combine Mock and Tank Model is Rain Flow PPE-PLN 01 Model. By calculating the parameters that represent watershed conditions in the river. In this research, trial and error procedur Solver Base Microsoft Excel program was used for calibrating rain flow model formula. Base on the results we can conclude some point. First, Reliability rain flow models (Model Mock and Tank) which has been calibrated for 2 years show the member square 3139,350 m3 and correlation 0.736 beetwean recorded discharge and the model discharge . second, from the parameters calculation which is calibrated using this applied model yield A1 = 0.019; A2 = 0.2957; B1 = 3828; B2 = 0702; Perco = 1.2285 mm / hr; KAIN = 64. 105 mm; KLAPANG = 23:12 mm; 26. ATAMP1 = 407 mm; ATAMP2 = 298.99 mm; KTAMP2 = 40 021 mm; CRO = 0.8; CSRO = 0.8. Third, the water availability in Samin River with 80% of discharge realibity computed by Rangking formula is 35216692438.56 m3 for one years and if computed by Weibull formula is 33406653559,944 m3 for one year.